Targeted differential photostimulation alters reproductive activities of domestic birds - Rozenboim, I.; Bartman, J.; Avital Cohen, N.; Mobarkey, N.; Zaguri, S.; El Halawani, M. E.; Chaiseha, Y.; Marco, A. (Frontiers in Physiology, 2022)
Modern poultry production systems are using environmental controlled houses providing only 14 artificial illumination. The role of light in reproduction of poultry depend on light quality 15 (photoperiod, intensity/brightness, and spectrum) which enables us to provide custom made 16 illumination, targeted for elevation of reproductive activities. Artificial targeted illumination 17 significantly affects poultry reproduction. This phenomenon is based upon the mechanism of light 18 absorption in birds consists of two main components: the eye (retinal photoreceptors) and brain 19 extraretinal photoreceptors. Several experiments on turkey hens, broiler breeder males and females 20 have shown that photostimulation of brain extraretinal photoreceptors, while maintaining retinal 21 photoreceptors under non-photostimulatory conditions elevates reproductive activity, by increasing 22 egg production of hens and semen quality of roosters. In addition, we found acceleration in all 23 gonadal axis parameters leading to the acceleration in production rate. Furthermore, we studied the 24 role of retinal activation on gonadal axis suppuration identified the role of serotonin in this 25 phenomenon. As for today several broiler breeder farms are using targeted illumination based on our 26 studies with excellent results.